Analysis of Quran Memorization Methods: Academically Talented Students - Gifa Oktavia; Burhanuddin Burhanuddin; Afifah Febriani; Zainal Asril; Syafrimen Syafril (Journal of Theory and Research Memorization Quran, 2025)
The activity of memorizing the Quran has existed since the time of the Prophet Muhammad because at that time the Prophet received the first revelation from the Jibril by memorizing. In Indonesia, memorizing the Quran is a very special and desirable thing. Many educational institutions ranging from kindergarten to college level have made tahfizh Alquran as their flagship program. However, in the learning process, students who are in this special class must have a special method or way of memorizing the Quran. Precisely, this study aims to analyze the method of memorizing the Quran for Academically Talented Students. This research uses a qualitative method using a case study approach. Data sources were taken from sixteen informants through in-depth interviews with informants. The sixteen informants consisted of the principal, vice principal for curriculum, tahfizh teacher and Academically Talented Students. This study found that there are three themes related to the method of memorizing the Quran for Academically Talented Students, namely: tikrar method, kitabah method and talaqqi method. This research can be used as a reference for educational institutions and teachers and guide Academically Talented Students in memorizing the Quran.